Eksplorasi Desain Logo NJP Bakery yang Efektif sebagai Upaya untuk Mencapai Konsistensi Branding - Fila Akbar Al Farizi; Aileena Solicitor Costa Rica El Chidtian; Prasetyo Adi Sulistyono (Journal of Creative Student Research, 2023)
NJP Bakery is a Micro, Small, and Medium-sized Enterprise (SMEs) dedicated to the production and sale of high-quality bread and pastry products. With a sharp focus on creating unforgettable culinary experiences for customers through authentic flavors and quality ingredients, NJP Bakery has evolved into the top choice for culinary enthusiasts who appreciate excellence. To further strengthen its image and brand, NJP Bakery is currently in need of a robust visual identity design. This visual identity includes a logo that not only reflects the core values of the company but also highlights the uniqueness of the offered products, successfully capturing the attention of the target market. Through a creative and representative design showcasing the premium quality of its products, this visual identity is expected to serve as a key differentiator for NJP Bakery in the market, while also contributing to the establishment of deep connections with its loyal customers.